DOP24 Japan prospective multicenter study for optimization of COVID-19 vaccinations based on the immune response and safety profile in Inflammatory Bowel Disease patients: Interim analyses of the J-COMBAT trial. (21st January 2022) - Watanabe, K; Hisamatsu, T; Nakase, H; Nagase, K; Matsuura, M; Aoyama, N; Kobayashi, T; Sakuraba, H; Yokoyama, K; Nishishita, M; Esaki, M; Hirai, F; et al.
Abstract: Background: Immune responses to the SARS-CoV-2 vaccination may be influenced by immunomodulatory drugs (IMDs). We investigated the immune responses and safety in fully vaccinated Japanese patients with IBD. Methods: IBD patients and control subjects at 39 institutes were invited to participate in the study from March to October 2021. Blood sample collections to measure anti-SARS-CoV-2 spike IgG antibody titers were planned pre-1st vaccination, pre-2nd vaccination, and at 4 weeks, 3 months and 6 months post-2nd vaccination. Immune responses were compared between groups, considering baseline characteristics and IMD treatments. (UMIN000043545) The interim analyses presented here include mainly data from the 4-weeks post-2nd vaccination time-point. Results: In total, 679 IBD patients and 203 controls were enrolled (Table 1). The IBD group received the BNT162b2 vaccine (86.2%) and the mRNA-1273 vaccine (12.5%), and the control group received the BNT162b2 vaccine (86.9%) and the mRNA-1273 vaccine (12.1%). Only 4 cases (0.7%) in the IBD group and 2 (1.0%) in the control group were infected with COVID-19. Adverse events of 2nd vaccination occurred in 48.4% of the IBD group and 35.1% of the control group. Comparison between administrated and non-administrated IBD patients for each IMD revealed an attenuated genomic mean titer (GMT [U/mL]) in those taking systemic steroids (18.85 vs 31.24), anti-TNF monotherapy (28.31 vs 42.99), anti-TNF therapy+ immunomodulator (IM) (12.86 vs 35.26), vedolizumab+IM (19.49 vs 30.39), ustekinumab+IM (20.44 vs 30.79), and tofacitinib (9.54 vs 32.08), but not in those taking oral 5-ASA (29.50 vs 32.40), or vedolizumab (41.85 vs 40.20) and ustekinumab (55.56 vs 39.26) monotherapies. Estimated least square means of the GMT by a multiple linear regression model are shown in Table 2. GMTs were significantly influenced by increasing age and allergy (51.2, 95%CI 42.1–62.3; p=0.0293), and tended to be influenced by COVID-19 infection (139.1, 41.0–472.2; p=0.0572). Sex, smoking, drinking, IBD, and adverse events of 2nd vaccination did not affect the GMT. The GMT was significantly higher for mRNA-1273 (90.3 [60.8–134.1]) than for BNT162b2 (39.6 [35.2–44.6], p= 0.0001). Systemic steroids (22.9 [13.9–37.7], p=0.0119), IM (24.2 [18.7–31.4], p<0.0001), anti-TNF agents (20.8 [15.3–28.3], p<0.0001), vedolizumab (25.2 [15.0–42.2], p=0.0409), ustekinumab (28.9 [18.5–45.0], p=0.0754), and tofacitinib (5.5 [2.8–10.9], p<0.0001), but not oral 5-ASA (39.1 [31.9–47.9], p=0.3225), attenuated GMTs at 4 weeks post-2nd vaccination (Table 2). Conclusion: Aging and most IMD options attenuated immunogenicity in fully vaccinated IBD patients. Prioritization of a booster vaccination should be considered for IBD patients treated with IMDs.